2015
DOI: 10.1017/s136898001500261x
|View full text |Cite
|
Sign up to set email alerts
|

A dose–response meta-analysis reveals an association between vitamin B12and colorectal cancer risk

Abstract: Objective: The current meta-analysis evaluated the association between vitamin B 12 intake and blood vitamin B 12 level and colorectal cancer (CRC) risk. Design: The PubMed and EMBASE databases were searched. A dose-response analysis was performed with generalized least squares regression, with the relative risk (RR) and 95 % CI as effect values. Setting: The meta-analysis included seventeen studies. Subjects: A total of 10 601 patients. Results: The non-linear dose-response relationship between total vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Some (10)(11)(12)(13)(14)(15) , but not all (16)(17)(18)(19)(20)(21)(22) , epidemiological studies reported an inverse association between folate intake and colorectal cancer risk. Similarly, inverse associations between vitamin B 2 , vitamin B 6 and vitamin B 12 and colorectal risk have been observed in some studies (23)(24)(25)(26)(27) . The evidence that methionine affects colorectal cancer is limited.…”
mentioning
confidence: 52%
“…Some (10)(11)(12)(13)(14)(15) , but not all (16)(17)(18)(19)(20)(21)(22) , epidemiological studies reported an inverse association between folate intake and colorectal cancer risk. Similarly, inverse associations between vitamin B 2 , vitamin B 6 and vitamin B 12 and colorectal risk have been observed in some studies (23)(24)(25)(26)(27) . The evidence that methionine affects colorectal cancer is limited.…”
mentioning
confidence: 52%
“…The majority of studies that looked at the role of B complex vitamins, primarily folate in oncogenesis were focused on C-1 metabolism (20,21). So far, studies are inconclusive on the role dietary intake of vitamin B 12 has in CRC (13)(14)(15)(22)(23)(24). Some studies showed positive relation between intake of vitamin B 12 and lower risk of CRC (13)(14)(15), while others showed no effect for other forms of gastric cancers (24).…”
Section: Vitamin B 12 and Carcinogenesismentioning
confidence: 99%
“…Sun et al (22) in their meta-analysis show that high total intake of vitamin B 12 (from diet and supplements combined) has an inverse relation with CRC risk if the intake is > 12 µg/day. Also, the association is stronger than if only dietary vitamin B 12 is considered.…”
Section: Dietary Intake Of Vitamin B 12mentioning
confidence: 99%
See 2 more Smart Citations